Tailoring the anion stoichiometry and oxidation kinetics of vanadium (oxy)nitride by the control of ammonolysis conditions - Laura I. V. Holz (2022)
Transition metal (oxy)nitrides are attractive materials due to their notable catalytic and electronic properties. Vanadium (oxy)nitrides, in particular, have generated high interest due to their wide applicability in heterogeneous catalysis, energy-related research (e.g., supercapacitors), and superconductors. One of the most promising ways to synthesize these materials is by ammonolysis. However, thermodynamic calculations predict that the chemical potentials of both the nitrogen and hydrogen precursors are dependent on the synthesis temperature, potentially influencing the N/O ratio of the formed (oxy)nitride. The current work, therefore, clarifies the effect of ammonolysis temperature on the (oxy)nitride composition and resultant physical properties. A series of vanadium (oxy)nitrides are formed by reacting V2O5 with gaseous ammonia in the temperature range 600-1000 degrees C. The synthesized materials are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetry (TGA), and X-ray photoelectron spectroscopy (XPS). The unit cell volume of the crystal is shown to increase with ammonolysis temperature, being concomitant with increased nitrogen incorporation. Kinetic analysis was performed by isoconversional and model-based methods, showing that the amount of incorporated nitrogen has a strong impact on materials stability, beneficially increasing the resistance towards oxidation. The work demonstrates that it is possible to compositionally tune the anionic sublattice of vanadium (oxy)nitride by controlling the ammonolysis temperature, where this method can be used as a tool to tailor resultant properties towards potential applications.